2016
DOI: 10.1116/1.4971991
|View full text |Cite
|
Sign up to set email alerts
|

Localized defect states and charge trapping in atomic layer deposited-Al2O3 films

Abstract: In this study, the authors compared different Al2O3 films grown by atomic layer deposition (ALD) with the same aluminum precursor but on different substrates. The authors employed different process parameters such as thermal-ALD and plasma-enhanced-ALD using different substrate temperatures ranging from 280 °C down to room temperature. They characterized these films by resonant photoelectron spectroscopy and by electrical measurements. They established that generally the ALD-Al2O3 films show characteristic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 91 publications
3
43
0
Order By: Relevance
“…[16][17][18][19][20][21][22] We have investigated the electronic properties of the Al 2 O 3 films prepared by different ALD processeso nd ifferent substrates. [16][17][18][19][20][21][22] We have investigated the electronic properties of the Al 2 O 3 films prepared by different ALD processeso nd ifferent substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] We have investigated the electronic properties of the Al 2 O 3 films prepared by different ALD processeso nd ifferent substrates. [16][17][18][19][20][21][22] We have investigated the electronic properties of the Al 2 O 3 films prepared by different ALD processeso nd ifferent substrates.…”
Section: Discussionmentioning
confidence: 99%
“…It is also supposed that the RT-ALD-Al 2 O 3 film deposited on CH 3 NH 3 PbI 3 at room temperature not only protects the perovskite film against environmental degradation but also that the excitonic states found in such films in our ChemSusChem 2018, 11,3640 -3648 www.chemsuschem.org previousw ork [20] help to maintain device performance at a constantl evel over al ong time. The investigations reported herein,a lso in comparison with the literature, highlight as ignificant influence of subnanometre-controlled processes performed on the perovskite film on the resulting solar-celle fficiency and stability.I tc an be concluded that, for improving the efficiency and stabilityo fp erovskite solar cells, not only is an Al 2 O 3 layer important but also suitable selection of its thickness (here, number of ALD cycles), preparation methoda nd process parameters (temperature, precursors, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not only do the TCO single crystals show these close relations, but the models presented here can be generalized also for amorphous films (magnetron sputtering in Ar/O 2 ) of the IGZO family 16,18,19,21 and also to several oxidic ALD films, [22][23][24][25]29 as all show similar behavior as they exhibit a high optical transparency and an n-type conductivity with high values of the mobility. In addition, these systems are easy to mix (IGZO family) while the properties remain stable.…”
Section: F Generalization For the Tco Family-an Outlookmentioning
confidence: 53%
“…The polarons are stabilized by lattice relaxations, which enable a strong hybridization of the valence states. Therefore, they are spread in energy into a wide band 22,23,29,33 in the valence regime. For the Ga 2 O 3 single crystal, the width of the polaron band is about 8 eV, as determined from the Fano analysis.…”
Section: A Atomic Model Of Intrinsic Defect Statesmentioning
confidence: 99%
“…Such films are grown directly on the MAPI surfaces without pretreatment; in particular, there is no need for an OH‐covered surface preparation . As a consequence, MAPI‐based PV devices showed recently an increase in long‐term stability and a protection against ambient conditions upon growth of ALD films of Al 2 O 3 at RT . Hence, the properties of such Al 2 O 3 films prepared at RT are of particular interest to improve the long‐term stability of MAPI PV devices without losing device performances.…”
Section: Introductionmentioning
confidence: 99%